Editor’s Note - Terdudomtham, Thamavit (Journal of Contemporary Social Sciences and Humanities, 2025)
The JCSH continues to focus on publishing research works on various contemporary issues in social sciences and humanities. In this issue, we are delighted to present seven (7) research articles from various academic disciplines. Several articles were related to vulnerable groups, including migrant workers, human trafficking victims, refugees, and asylum seekers. In the first article, Shwe Zin Thin and Sasiphattra Siriwato investigated the situation of migrant workers in the Thai fishing industry after Thailand’s ratification of the ILO Work in Fishing Convention (C188) in Ranong Province. Based on a semi-structured interview method, the authors concluded that Thailand’s fishing industry has not adhered to the C188 standards. For example, fishers lacked proper health and safety training, did not receive adequate protection or compensation for injuries at work, and experienced violations of payment law. In the second article, Siriluck Wiriyadee and Thamavit Terdudomtham studied the challenges, personal factors influencing the needs, and cooperation of human trafficking victims, in order to give policy recommendations for victim-centered proceedings. Based on a mixed-methods approach, the authors found that personal factors of victims significantly affected their needs and cooperation. The authors pointed out that a victim-centered justice system sought to empower victims by addressing their specific needs, reducing re-traumatization, and mitigating the imbalance of power between victims and state authorities, which manifested in procedural delays and a lack of agency for victims in legal proceedings.